Social Media Usage and the Academic Engagement of Junior High School Students in Northwestern Ghana - Puobanye, Christiana; Siita, Niamatu; Seidu, Emelia (South Sulawesi Education Development, 2026)
Despite the growing prevalence of social media among adolescents, limited research has examined its direct impact on academic engagement among Junior High School (JHS) students in underserved contexts. While prior studies have explored social media’s effects on academic performance, procrastination, and peer interaction, few have investigated how students’ digital behaviours influence engagement in learning activities, highlighting an important empirical gap. This study argues that social media exerts a dual influence, simultaneously enabling learning through collaboration and access to educational resources, while also fostering distraction and superficial learning. Guided by the research question,